Transformasi Teknologi Finansial dan Implikasinya terhadap Dinamika Perkembangan Perbankan Syariah di Kawasan Asia Tenggara - Muh. Nur; David Christian Engelbert Lisapaly; Ummy Kalsum (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the implications of financial technology transformation on the dynamics of Islamic banking development in Southeast Asia using a descriptive-comparative qualitative approach. Secondary data were obtained from industry reports such as Asia Business Outlook, UOB Group, and Asian Banking & Finance, which highlight fintech growth and Islamic financial assets in the ASEAN region. The findings reveal that digitalization through fintech enhances operational efficiency, expands financial inclusion, and strengthens transparency in Islamic finance systems. Islamic banks in Indonesia and Malaysia have pioneered the adoption of technologies such as blockchain and artificial intelligence to maintain compliance with Sharia principles while improving competitiveness. Despite challenges related to regulation, cybersecurity, and human capital readiness, the synergy between digital innovation and Islamic values has reinforced the resilience of the regional Islamic banking sector. This transformation underscores that the future of Islamic banking in Southeast Asia depends on integrating technological efficiency with social justice and the ethical foundations of Islamic finance.